2000
DOI: 10.1128/jvi.74.4.1775-1780.2000
|View full text |Cite
|
Sign up to set email alerts
|

Abundant Defective Viral Particles Budding from Microglia in the Course of Retroviral Spongiform Encephalopathy

Abstract: A pathogenetic hallmark of retroviral neurodegeneration is the affinity of neurovirulent retroviruses for microglia cells, while degenerating neurons are excluded from retroviral infections. Microglia isolated ex vivo from rats peripherally infected with a neurovirulent retrovirus released abundant mature type C virions; however, infectivity associated with microglia was very low. In microglia, viral transcription was unaffected but envelope proteins were insufficiently cleaved into mature viral proteins and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Microvessels of the CNS constitute a complex anatomical structure composed of endothelial cells, perivascular monocytes, pericytes, and astrocytes, that together form a dynamic structural and metabolic barrier to maintain normal brain function 38,39 . Among these constituents of the BBB, it is suggested that microglia have a key role in the manifestation of neuropathogenicity induced by the neuropathogenic retroviral infection 40–42 . Despite a report showing an increase in cytokine expression in the brains of infected animals after neuropathogenic retro‐viral infection of the endothelia and microglia, 43 we found a certain degree of immuno‐suppression caused by retroviral infection.…”
Section: Discussionmentioning
confidence: 60%
“…Microvessels of the CNS constitute a complex anatomical structure composed of endothelial cells, perivascular monocytes, pericytes, and astrocytes, that together form a dynamic structural and metabolic barrier to maintain normal brain function 38,39 . Among these constituents of the BBB, it is suggested that microglia have a key role in the manifestation of neuropathogenicity induced by the neuropathogenic retroviral infection 40–42 . Despite a report showing an increase in cytokine expression in the brains of infected animals after neuropathogenic retro‐viral infection of the endothelia and microglia, 43 we found a certain degree of immuno‐suppression caused by retroviral infection.…”
Section: Discussionmentioning
confidence: 60%
“…The data presented above indicate that ecotropic Env targeting of a neurotoxic Env is sufficient for inducing neurodegeneration; however, the specific CNS targets responsible for disease induction remain obscure. Given that microglia constitute a major CNS target of MLVs (3,4,20,21,30,32,34), we examined these cells for the expression of CasBrE and Friend Envs to assess the capacity of the packaging NSCs to infect host targets. In this regard, transplanted SFF-FE-gpgpt NSCs resulted in significant Env expression in microglia by 21 dpi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess whether CNS delivery of env alone could induce spongiform disease, NSCs were engineered into retroviral packaging cells capable of producing infectious but replication-incompetent virus encoding the CasBrE Env protein (SU/TM). Transplantation of these packaging NSCs failed to induce acute spongiosis, despite env dissemination to, and ex-pression within host microglia (33), a major CNS target of MLVs (3,4,20,21,30,52). These latter experiments suggested that MLV-induced spongiform neuropathogenesis might require host cell expression of certain non-Env retroviral proteins or, alternatively, the disease might require CasBrE env virus delivery to, and protein expression within, host cells other than, or in addition to, microglia.…”
mentioning
confidence: 99%
“…Thus, it appears likelier that these responses were derived from the infected cells in the brain stem. (17,33). These results are similar to processing defects described here that were encountered in the use of infected NIH 3T3 cells, suggesting that infected microglia are also undergoing ER stress.…”
Section: Discussionmentioning
confidence: 99%